Fabrication of PANI-coated honeycomb-like MnO2 nanospheres with enhanced electrochemical performance for energy storage. (20th October 2015) - Sun, Xiaowu; Gan, Mengyu; Ma, Li; Wang, Huihui; Zhou, Tao; Wang, Shiyong; Dai, Wenqin; Wang, Huining
Graphical abstract: Highlights: Honeycomb-like MnO2 nanospheres serve as a scaffold for polyaniline. Polyaniline act as a protective coating layer to restrain MnO2 nanospheres from dissolution in acidic electrolyte. The obtained composite exhibits a high capacitance of 565 F g −1 (specific capacity of 126 mAh g −1 ) at the current density of 0.8 A g −1 in 0.5 M Na2 SO4 -0.5 M H2 SO4 solution. Abstract: A new binary composite of MnO2 /PANI has been synthesized as electrode material for energy storage. In the composite, the MnO2 nanospheres with a honeycomb-like structure are coated with PANI layers, in which MnO2 serve as a scaffold for PANI layer and PANI act as a protective coating layer to restrain MnO2 nanospheres from dissolution in acidic electrolyte, and causing a synergic effect. The composite, when the mass ratio of MnO2 and aniline is 1:1, exhibits a high specific capacitance of 565 F g −1 (specific capacity of 126 mAh g −1 ) at a discharge current density of 0.8 A g −1 and a high specific capacity of 143 mAh g −1 at the scan rate of 20 mV s −1 in 0.5 M Na2 SO4 -0.5 M H2 SO4 solution. In addition, the electrode material retains about 77% of the initial capacitance after 1000 cycles of charge-discharge at 8 A g −1 . These results demonstrate that the special morphology and shorter diffusion pathways (SEM and EIS) make the binary composite a promising candidate for future energy storage applications.